Santa Claus : law, Fourth Industrial Revolution, decolonisation and Covid-19 - Mpedi, Letlhokwa George (Sun OA, 2020)
"The origins of Santa Claus, or so I am told, is that the young Bishop Nicholas secretly delivered three bags of gold as dowries for three young girls to their indebted father to save them from a life of prostitution. Armed with immortality, a factory of elves and a fleet of reindeer, his has been a lasting legacy, inextricably linked to Christmas. Of course, this Christmas looks a little different. Amidst a global pandemic, shimmying down the chimneys of strangers certainly does not adhere to social distancing guidelines. Some borders remain closed, and in some instances, the quarantine period is far too long. After all, he only has 24 hours to spread cheer across the world. As with the rest of us, Santa Claus is likely to get the remote working treatment. The reindeers this year are likely to be self-driving, reminiscent of an Amazon swarm of technology, and the naughty and nice lists are likely to be based on algorithms derived from social media accounts. In the age of the fourth industrial revolution, it is difficult to imagine that letters suffice anymore. How many posts were verified as real before shared? Enough to get you a drone. Fake news? Here is a lump of coal. Will we see elves in personal protective equipment (PPE) and will Santa Claus, high risk because of age and his likely comorbidities from the copious amount of cookies, have to self-isolate in the North Pole? In fact, will there be any toys at all this year? Surely production has been stalled with the restrictions on imports and exports into the North Pole. Perhaps, there is a view to outsourcing, or perhaps, there is a shift towards local production and supply chains. More importantly, as we have done in many instances in this period, maybe we should pause to reflect on the current structures in place. The sanctification of a figure so clearly dismissive of the Global South and to be critical, quite classist must be called into question. From some of the keenest minds, the contributions in this book make a strong case against this holly jolly man. We traverse important topics such as, is the constitution too lenient with a clear intruder who has conveniently branded himself a Good Samaritan? Allegations of child labour under the guise of elves, blatant animal cruelty, constant surveillance in stark contrast to many democratic ideals and his possible threat to national security come to the fore. Nevertheless, as the song goes, he is aware when you are asleep, and he knows when you are awake. Is feminism a farce to this beloved man - what role does Mrs Claus play and why are there inherent gender norms in his toys? Then is the worry of closed borders and just how accurate his COVID-19 tests are. Of course, this brings his ethics into question. While there is an agreement that transparency, justice and fairness, nonmaleficence, responsibility, and privacy are the core ethical principles, the meaning of these principles differs, particularly across countries and cultures. Why are we subject to Santa Claus' notions of good and evil when he is so far removed from our context? As Richard Thaler and Cass Sunstein would tell you, this is fundamentally a nudge from Santa Claus for children to fit into his ideals. A nudge, coined by Thaler, is a choice that predictably changes people's behaviour without forbidding any options or substantially changing their economic incentives. Even with pinched cheeks and an air of holiday cheer, Santa Claus has to come under scrutiny. In the process of decolonising knowledge and looking at various epistemologies, does Santa still make the cut?"-- Provided by publisher.
Keywords: Santa Claus -- (Fictitious character) -- History.; Santa Claus -- (Fictitious character) -- Anecdotes.; Santa Claus -- (Fictitious character); Social change.; Law -- South Africa -- Philosophy.; Industry 4.0.; Decolonization.; Industrialization.; COVID-19 (Disease); Law -- Philosophy.; South Africa.; Anecdotes.; History.; Electronic books.